Development of a Preventive Long-Term Care System for the Elderly by the Individual Wellness Plan in the Community - Banpoun, Vimol; Jenjitr, Juthapuk; Suebsak, Wanpinan (Journal of Preventive Medicine Association of Thailand, 2021)
This study aimed to develop a preventive long-term care system for the elderly by the individual wellness plan in the community, which was performed in 3 steps: The preparation, the operation, and the performance tracking. A mixed-method study was used to collect quantitative data from a sample group of 1,074 people covering all four regions of the country and analyzed by descriptive statistics, and qualitative data carried out through in-depth interviews with elderly and selected one province for each region, namely Uttaradit, Nakhon Nayok, Khon Kaen, and Songkhla provinces. The content was analyzed according to the specified issues. This study was conducted during September 2019 and October 2020. The preventive long-term care system formats for the elderly were the guidelines according to the manual for health workers and the elderly, health care promotion plan for the individual elderly in the community, and the human resource development “Kru Kor.” The operating results revealed that 80 percent of the elderly received comprehensive health advice, especially about disease handling and prevention, and 8 out of 10 elderly received the health screening, including the assessment of activities of daily living (ADL) and exercise. Most elderly mentioned that this individual wellness plan was very useful, practical, and had a good and consistent transfer process. The individual wellness plan form can be recorded, so it serves as a reminder to practice good health behaviors. The content of guidelines for the elderly health promotion should be developed by integrating with the relevant agencies as well as the guidelines for knowledge transfer of health care for the elderly should be developed by building cooperation of network partners and other sectors and promoting the elderly to the health literacy.